"Upholding the Correct Political Direction". The PLA Reform and Civil-Military Relations in Xi Jinping's China. Issue 3 (3rd July 2018) - Dossi, Simone
Abstract: The military reform launched in late 2015 has significant implications for China's civil-military relations. One of the stated goals of the reform is to "uphold the correct political direction" by strengthening party control over the People's Liberation Army. This has been achieved by centralising power over the PLA in the hands of the Central Military Commission, while at the same time centralising power within the Commission in the hands of its Chairman. This dual centralisation of power might considerably change the way in which the 'conditional compliance' model of civil-military relations works in Xi Jinping's China.